2017
DOI: 10.15252/emmm.201607296
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of F4L (ribonucleotide reductase) in vaccinia virus produces a selective oncolytic virus and promotes anti‐tumor immunity with superior safety in bladder cancer models

Abstract: Bladder cancer has a recurrence rate of up to 80% and many patients require multiple treatments that often fail, eventually leading to disease progression. In particular, standard of care for high‐grade disease, Bacillus Calmette–Guérin (BCG), fails in 30% of patients. We have generated a novel oncolytic vaccinia virus (VACV) by mutating the F4L gene that encodes the virus homolog of the cell‐cycle‐regulated small subunit of ribonucleotide reductase (RRM2). The F4L‐deleted VACVs are highly attenuated in normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 55 publications
(74 reference statements)
0
38
0
Order By: Relevance
“…This pattern suggests that the cellular TK1 level might not be the main determinant of VACV and OVV replication for all cancer cell lines. It is known that other mechanisms, such as extracellular signal-regulated kinase (ERK) [32] and ribonucleotide reductase (RR) [33] expression, can also influence viral replication in cancer cells. Consequently, different double-gene deletion strategies have been applied to further improve the tumor selectivity of OVV [8,22].…”
Section: Discussionmentioning
confidence: 99%
“…This pattern suggests that the cellular TK1 level might not be the main determinant of VACV and OVV replication for all cancer cell lines. It is known that other mechanisms, such as extracellular signal-regulated kinase (ERK) [32] and ribonucleotide reductase (RR) [33] expression, can also influence viral replication in cancer cells. Consequently, different double-gene deletion strategies have been applied to further improve the tumor selectivity of OVV [8,22].…”
Section: Discussionmentioning
confidence: 99%
“…However, viral dissemination ability does not correlate with viral replication ability, as in this study, dissemination-enhanced WI virus demonstrated markedly lower replication than the wild-type WR virus in the two cell lines tested. The reduced viral replication is likely caused by the deletion of the TK gene [22,23]. Therefore, due to the deletion of the TK gene, as well as to the insertion of the IFNB1 gene, SJ-815 has both reduced viral replication and dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has shown arming vaccinia viruses with therapeutic cytokines achieved efficient development in diverse cancers. [21][22][23] In this study, we successfully constructed recombinant VV-IL37 and examined the ability of VV-IL-37 to destroy HCC, both in vitro and in vivo. We found that treatment with VV-IL-37 significantly inhibited tumor growth, which might provide an effective treatment strategy for HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller tumors were observed in VV-IL-37-GFP group relative to VV-mock-GFP. [21][22][23] In this study, we successfully constructed recombinant VV-IL37 and examined the ability of VV-IL-37 to destroy HCC, both in vitro and in vivo. Western blot results revealed that VV-IL-37-GFP infection promoted IL-37 protein expression in HCC mice (Fig.4B).…”
Section: Vv-il-37 Infection Represses Hcc Growth In Vivomentioning
confidence: 99%